PENYULUHAN MANFAAT PERASAN BUAH MENGKUDU DALAM MENURUNKAN HIPERTENSI - Hariati Hariati; Sulastri Ginting; Zuliawati Zuliawati; Rentawati Purba; Dewi Tiansa Barus (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Hypertension is a state of increasing blood pressure beyond normal limits. Hypertension is often accompanied by symptoms that cause discomfort to the sufferer. The symptoms experienced are headache, palpitations, difficulty breathing, fatigue and blurred vision. To lower blood pressure to reduce the symptoms felt can be done by using noni fruit. Iuni action is very practical, cheap and easy and can be done by everyone. This action is still rarely performed by patients in the community when experiencing increased blood pressure. The service was carried out on 15 people who had hypertension. The service implementation team provided training on how to process noni in the work area of ​​the Patumbak Health Center. The team made home visits as an evaluation of the service program. The outreach activities went smoothly. There were 5 patients who asked about the counseling material. The importance of conducting regular outreach activities to the community about other complaints they suffer to improve their health status.